Carbon nanotube arrays decorated with multi-layer graphene-nanopetals enhance mechanical strength and durability. (April 2015) - Kumar, Anurag; Maschmann, Matthew R.; Hodson, Stephen L.; Baur, Jeffery; Fisher, Timothy S.
Abstract: We report growth of a hierarchical nanostructure consisting of multi-layer graphene-petals decorating individual carbon nanotubes in a vertically aligned CNT array. The structure obtained by post-growth treatment of the CNT array in a microwave plasma chemical vapor deposition process leads to a remarkable increase in array stability, stiffness, elastic recovery and energy absorption capacity and a decrease in stress softening. Further, the change in properties can be tuned by controlling the petal growth time. For a 50 μm tall array, growth of graphene petals increases the buckling load and energy absorbed in load–unload cycles by a factor of about 60. The petal-coated CNT arrays also retain their morphology during solvent immersion and evaporation cycles, while arrays without petals coalesce into highly dense regions. The results open a new pathway towards tuning mechanical behavior of any arbitrary CNT array and also demonstrate the importance of structural hierarchy in tailoring the behavior of nanostructures.